2020
DOI: 10.1590/0103-11042020e222
|View full text |Cite
|
Sign up to set email alerts
|

Vigilância em saúde e desastres de origem natural: uma revisão da literatura

Abstract: RESUMO As projeções climáticas para o final do século XXI sugerem a intensificação de eventos extremos que podem causar danos diretos e indiretos à saúde pública e impactar, em diferentes proporções, as populações vulneráveis. Nesse âmbito, destaca-se a vigilância em saúde por suas relevantes ações em todas as etapas de gestão de risco dos desastres. O objetivo deste artigo foi realizar uma revisão da literatura científica sobre a vigilância em saúde e desastres de origem natural, com intuito de descrever as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In this sense, previous studies in Brazil have shown the importance of the Brazilian Ministry of Health in such emergency situations. However, the country still faces challenges such as human resources and capacity for timely action and even awareness of the vulnerable communities regarding disaster risk 20,21 . Furthermore, health surveillance, especially in hydrological disasters, must occur in a coordinated manner with the various levels of healthcare to reduce and control the impacts of disasters on public health 22 .…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, previous studies in Brazil have shown the importance of the Brazilian Ministry of Health in such emergency situations. However, the country still faces challenges such as human resources and capacity for timely action and even awareness of the vulnerable communities regarding disaster risk 20,21 . Furthermore, health surveillance, especially in hydrological disasters, must occur in a coordinated manner with the various levels of healthcare to reduce and control the impacts of disasters on public health 22 .…”
Section: Discussionmentioning
confidence: 99%
“…In this context, a study revealed that the effects of natural disasters on health represented an important challenge for public health due to its several derived factors (e.g., vulnerability of the population and the economic development model adopted, which often affects the climate) and required a coordinated risk management action among all levels across health sectors [87].…”
Section: Class 1 -Assessment Of Coverage Accessibility Quantity and D...mentioning
confidence: 99%